IL-7/αIL-7 mAb M25 immunocomplexes expand CD8+ T cells but paradoxically abrogate the antitumor activity of CTLA-4 and PD-1 blockage. (September 2020) - Hrabos, Dominik; Hnizdilova, Tereza; Tomala, Jakub; Uhlik, Jiri; Kovar, Marek
Highlights: IL-7/M25 shift the CD8+:CD4 + T cell ratio in favor of CD8 + T cells. IL-7/M25 and checkpoint inhibitors increase the infiltration of tumor by CD8 + T cells. IL-7/M25 significantly abrogated the antitumor activity of αCTLA-4 plus αPD-1. Abstract: Supraphysiological levels of IL-7 induce increase counts of pre-B cells, naive T cells and memory phenotype CD8 + T cells. Immunocomplexes of IL-7 and αIL-7 mAb M25 (IL-7/M25) were described as IL-7 superagonist in vivo . Thus, treatment of mice with IL-7/M25 remarkably increases the size of the T cell pool. We decided to use IL-7/M25 in order to expand the T cell population prior to the administration of αCTLA-4 and αPD-1 mAbs in tumor-bearing mice and in turn boost the immunotherapy based on a combination of CTLA-4 and PD-1 blockage. We found that just four doses of IL-7/M25 increased the absolute numbers of splenocytes approximately fivefold and significantly shifted the CD4 + :CD8 + T cell ratio in favor of CD8 + T cells. There was also a substantive increase in relative counts of memory phenotype CD8 + T cells (approximately threefold) within CD8 + T cells but a significant decrease (approximately 30%) in relative counts of Treg cells within CD4 + T cells. All these data suggest that IL-7/M25 offer a suitable approach to potentiate tumor immunotherapy through CTLA-4 and PD-1 blockage. Unexpectedly, IL-7/M25 significantly abrogated the antitumor activity of αCTLA-4 plus αPD-1 mAbs in the following mouse tumor models: MC-38 and CT26 colon carcinoma and B16F10 melanoma. This paradoxical effect of IL-7/M25 on the antitumor activity of CTLA-4 and PD-1 blockage was not mediated via either increased levels of IL-10 or TGF-β in the sera or increased counts of IL-10-producing B or T cells in the spleen of mice injected with IL-7/M25. Thus, our work shows that caution should be exercised when combining two immunotherapy approaches together.